KINESITHERAPEUTIC APPROACH IN PATIENTS WITH ISCHEMIC STROKE TREATED WITH VENOUS THROMBOLYSIS - Mariela Filipova; Daniela Popova; Stanislava Bogomilova; Gergana Nenova (Peytchinski Publishing, 2020)
Ischemic stroke is a social disorder that leads to a great degree of disability in the world. In recent years, in undeclared practice, new methodologies and assessment methods have been introduced that are not presented with regard to the possibility of determining the potential potential of individuals in choosing a stroke. Methods: A total of 205 patients with ischemic stroke with a pronounced motor deficiency were investigated after an acute incident. Everyone has a history, clinical and paraclinical examinations, motor deficit and kinesitherapeutic potential. Results and analysis: The result of the registration of the registered persons, which are intended for the best and best assessment of the condition. Conclusion: In conclusion, we can say that the assessment is complex and the use of single tests is not appropriate. For the proper determination of the kinesitherapeutic potential, specialized tests should be used, which in turn provide a qualitative and rapid analysis of the condition of the patients.